William F. Winter and the new Mississippi : a biography - Bolton, Charles C. (Willie Morris books in memoir and biography., 2013)
For more than six decades, William F. Winter (b. 1923) has been one of the most recognizable public figures in Mississippi. His political career spanned the 1940s through the early 1980s, from his initial foray into Mississippi politics as James Eastland's driver during his 1942 campaign for the United States Senate, as state legislator, as state tax collector, as state treasurer, and as lieutenant governor. Winter served as governor of the state of Mississippi from 1980 to 1984. A voice of reason and compromise during the tumultuous civil rights battles, Winter represented the earliest embodiment of the white moderate politicians who emerged throughout the "New South." His leadership played a pivotal role in ushering in the New Mississippi: a society that moved beyond the racial caste system that had defined life in the state for almost a century after emancipation. In many ways, Winter's story over nine decades is also the story of the evolution of Mississippi in the second half of the twentieth century. This biography traces his life and influences from boyhood days in Grenada County, through his service in World War II, and through his long career serving Mississippi.